Iliopsoas Hemorrhage in Pediatric Patients with Hemophilia, Experience from One Centre - Turkkan, Emine; Atay, Didem Yalcin; Ocak, Suheyla; Ozdemir, Gul Nihal (AMER SOC HEMATOLOGY, 2015)
57th Annual Meeting of the American-Society-of-Hematology, Orlando, FL, DEC 05-08, 2015